Penerapan Metode SAW Pada Rekomendasi Pemilihan Jenis Jamur Untuk Budidaya Dan Konsumsi - Nurrohim, Muhammad; Lestariningsih, Endang; Nurraharjo, Eddy (STIKOM Tunas Bangsa Pematangsiantar, 2022)
Advances and developments in technology are currently getting faster, because technology has many uses. One of them is technology is used to assist in making decisions. The aim of this research project is to design and build a decision support system to determine which mushroom plants can be cultivated and consumed safely, resulting in a recommendation system for selecting mushroom species for cultivation and consumption for users or the community. In recent years, mushrooms have become a hot topic of conversation in Indonesia. Currently, people in Indonesia are starting to like to consume various processed foods made from consumption mushrooms. So that the raw material for production, namely mushrooms, is needed quite a lot. In the end, several elements of society began to peek at business opportunities to cultivate consumption mushrooms to earn income. The method that will be applied in the system is the SAW (Simple Additive Weighting) method. The workings of the method is to perform calculations, namely calculating the weighted number of rating criteria on all attributes in each alternative then producing the largest value which is selected as the best alternative and a thorough ranking is carried out. The results obtained are for oyster mushrooms to be ranked as the best alternative with the largest value of 23